The mediating effect of customer experience on word of mouth and repurchase behaviours in mobile payment services in Tanzania - Pamela Liana; Jan-Erik Jaensson; Goodluck Mmari (Cogent Business & Management, 2024)
One of the biggest drivers of Tanzania's economy, inclusion in the digital financial system, and reaching the unbanked population nationwide is mobile payment services. Due to the development of mobile banks and the dynamics of digital technology advances, which make it challenging to comprehend consumer behaviours, the sector, which is served by telecom firms, suffers intense competition. Unfortunately, the topic hasn't received much attention from marketing professionals, thus this study will focus on examining the connection between service quality and word-of-mouth mediated by customer experience. The second is to investigate how customer experience, through service quality, influences repurchases behaviour. With a sample of 379 Dar Es Salaam residents who utilize mobile payments, the study took a positivist stance. Moreover, the study employed convenient sampling techniques, and the data were analysed with Smart PLS 4. The analysis involved a reflective-formative measure of constructs in lower- and higher-order models and a bootstrapping method for the mediating analysis. The hypotheses were tested and revealed a significant positive relationship between the specific indirect effects of service quality and positive word of mouth and repurchasing intention. The study contributes to the digital financial service marketing sector and recommends that policymakers and managers substantiate customer experience for better communication and marketing strategies.
Keywords: 650; Customer experiences; service quality; word of mouth; repurchase behaviours; mobile payment